(untitled) (Swiss Medical Weekly, 2017)
QUESTION UNDER STUDY Switzerland has been receiving migrants of various origins for more than 50 years. The adoption of risk-taking behaviours among migrant youths is unclear. Moreover, when studied, migrant youths are rarely analysed according to whether they are first or second generation, or just young people with mixed origins. The aim of this study was to assess whether there are any differences between first-and second-generation immigrants, youths of mixed origins and their native peers in Switzerland concerning their engagement in risk behaviours. METHODS A total of 5834 youths from eleven post-mandatory schools in the canton of Fribourg (Switzerland) participated in the baseline survey of the GenerationFRee study, a longitudinal study to assess their lifestyle. Participants were divided by gender and by origin into: (a) natives: Swiss-born youths with Swiss-born parents, (b) first-generation migrants: foreign-born youths with foreign-born parents, (c) second-generation migrants: Swiss-born youths with foreign-born parents, (d) mixed-origin youths: Swiss-born youths with one Swiss-born parent and one foreign-born parent. Participants reported personal, family and school information, and attitudes towards eight risk behaviours. All significant variables at the bivariate level were included in a binary logistic regression. RESULTS The logistic regression showed that, compared with natives, first-and second-generation migrant boys were less likely to misuse alcohol. Boys of mixed origins were similar to migrants, although at the bivariate level they were more exposed to risk behaviours than were migrants. First-and second-generation migrant girls were less likely to misuse alcohol but three times more likely to be excessive Internet users. Girls of mixed origin were more likely to have their parents not living together and reported antisocial behaviours almost twice more often. CONCLUSIONS Our findings expose a lower engagement in risk behaviours among migrants. The migrant status in these two groups is clearly buffered if other control variables are considered. Thus, we can affirm that in the present study, migrants are not a high-risk population or not more at risk than the native group. Mixed origin youths showed higher risk behaviours than natives and migrants. Special attention should be given to this specific group, as they may be more vulnerable during adolescence.